2022
DOI: 10.1002/er.8617
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally compatible 3‐dimensional star‐shaped donor materials for efficient organic solar cells

Abstract: Small molecule (SM)-based star-shaped materials are getting tremendous attention to be employed as hole transport materials for organic/perovskite solar cells (OSCs) due to their tunable energy levels, intense absorption ability, and their three-dimensional (3D) charge transport properties. Herein, fourarmed SM donors (BD1-BD10) with benzodithiophene (BDT) as the centralcore unit have been efficiently designed and then characterized theoretically to investigate their optical and optoelectronic behavior. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In contrast, the LUMO charging density across all the studied molecules (R and SA1–SA5) is noted to be partially spread in the central core unit and high density in end‐cap acceptors. Among all the proposed molecules, the HOMO level value is lower as compared with the R molecule value, showing excellent charge transfer and electrical conductivity in these designed molecules 27–30 . Thus, these designed molecules (SA1–SA5) may be a reliable source of a high PCE value.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In contrast, the LUMO charging density across all the studied molecules (R and SA1–SA5) is noted to be partially spread in the central core unit and high density in end‐cap acceptors. Among all the proposed molecules, the HOMO level value is lower as compared with the R molecule value, showing excellent charge transfer and electrical conductivity in these designed molecules 27–30 . Thus, these designed molecules (SA1–SA5) may be a reliable source of a high PCE value.…”
Section: Resultsmentioning
confidence: 94%
“…Among all the proposed molecules, the HOMO level value is lower as compared with the R molecule value, showing excellent charge transfer and electrical conductivity in these designed molecules. [27][28][29][30] Thus, these designed molecules (SA1-SA5) may be a reliable source of a high PCE value. So, these designed molecules may be efficient than the reference because of the increased charge transfer capacity.…”
Section: Frontier Molecular Orbitalmentioning
confidence: 99%
“…For V oc calculations, PC61BM was selected for effective electron injection from donor molecules to the acceptor (PC61BM). Research has shown that electron injection efficiency from the HOMO orbital of the donor molecule to the LUMO of the acceptor is maximized when the ELL values are between 0.2 and 1 eV . All of the proposed molecules had ELL in the highly competitive range of 0.42–0.95 eV except for a bit of divergence in the energies of AS1, AS3, and AS7, and their values are 1.25, 1.16, and 1.05 eV.…”
Section: Resultsmentioning
confidence: 98%
“…LHE is significantly related to oscillator strength, ultimately affecting the production of short-circuit current ( J sc ). Thus, the efficiency of solar devices is highly influenced by their ability to harvest sunlight. , Equation was used to calculate the LHE of all currently studied molecules LHE = 1 10 f where “ f ” corresponds to the oscillator strength in the solvent phase of molecules.…”
Section: Resultsmentioning
confidence: 99%